Analisis Kesantunan Berbahasa Dalam Serial Animasi Riko The Series - Melsari, Pia; Widjojoko, Widjojoko; Wardana, Deni (Universitas Pendidikan Indonesia Kampus Serang, 2021)
Politeness in language is an important aspect that needs to be considered in order to create good communication. The development of technology following the changing times has an impact, one of which is the way humans communicate. The loss of ethics in language has occurred in today's society, so that special attention is needed regarding politeness in language. Formal and informal education have a big role to play in instilling ethical values and politeness. The habit of using polite language needs to be trained and instilled as early as possible. Films can be used as a means of habituating the use of polite language. So that the selection of a film needs to be considered and analyzed. This study aims to describe the principles of politeness in the animated series Riko The Series. This research focuses on obeying and violating the principles of politeness based on Leech's theory. This study uses a qualitative approach with content analysis methods that utilize the transcript of the characters in the animated series Riko The Series. In this study, data on the animated series Riko The Series contained 33 utterances that adhere to language politeness, namely 7 wisdom maxim. 7 maxims of generosity, 6 maxims of appreciation, 7 maxims of simplicity, 4 maxims of consensus, 4 maxims of sympathy. Furthermore, there are 14 utterances that violate the principle of Leech's politeness including 3 maxim of wisdom, 2 maxim of generosity, 3 maxim of appreciation, 4 maxim of simplicity, 1 maxim of consensus, 1 maxim of sympathy.